1999
DOI: 10.1002/(sici)1097-4547(19990401)56:1<93::aid-jnr12>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Manganese uptake into rat brain during development and aging

Abstract: Manganese (Mn) is an essential metal and plays an important role in the brain. To evaluate Mn uptake into the brain during development and aging, 54Mn concentrations in the brain of rats aged from 5 days to 95 weeks were measured after injection of 54MnCl2. 54Mn concentration in the brain of 5-day-old rats was the highest of all age groups tested. The liver and blood of 5-day-old rats also showed the highest 54Mn concentrations among the age groups. These results suggest that Mn is required in a high amount du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…70,77) The radioactivity from transferrin-bound 54 Mn in the brain was the lowest of all three substrates. Transferrin receptors are present on the surface of brain capillary endothelial cells.…”
Section: ) 54mentioning
confidence: 94%
See 1 more Smart Citation
“…70,77) The radioactivity from transferrin-bound 54 Mn in the brain was the lowest of all three substrates. Transferrin receptors are present on the surface of brain capillary endothelial cells.…”
Section: ) 54mentioning
confidence: 94%
“…70) Dietary manganese deficiency might affect manganese homeostasis in the brain, as evidenced by increased susceptibility of manganese-deprived rats to convulsions. 71) Carl et al indicated that manganese concentrations in tissues including the brain are increased after epileptic seizures.…”
Section: Manganesementioning
confidence: 99%
“…This element is very important for the normal functioning of the nervous system [16,[34][35][36]. The enzymes that contain magnesium provide energy and plastic processes in the CNS, participate in ATP hydrolysis, maintain the activities of Mg,Ca ATPases, and are involved in the synthesis of neuropeptides [21,37,38].…”
mentioning
confidence: 99%
“…Collectively, transport studies suggest that MnCI2 enters the brain from the blood either across the cerebral capillaries and/or the cerebrospinal fluid (CSF). At normal plasma concentrations, Mn enters the CNS primarily across the capillary endothelium, whereas at high plasma concentrations, transport across the choroid plexus predominates (14,(29)(30)(31)(32)(33).…”
mentioning
confidence: 99%
“…For example: a) both metals are transition elements adjacent to each other in the Periodic Table; b) both carry similar valence charges (2+ and 3+) in physiological conditions; c) both have similar ionic radius; d) both strongly bind Tf (3,14,22), and e) intracellularly, both preferentially accumulate in mitochondria (43,44 …”
mentioning
confidence: 99%